Navigating Digital Careers: A Multi-Case Study of Women’s Career Decisions in Indonesia’s IT Sector - Rinda Faiz Shabira; Mahendrawathi ER (Journal of Information System and Informatics, 2026)
Indonesia’s rapid digital transformation has intensified demand for IT talent, yet female attrition remains high. Aligning with the Sustainable Development Goals’ emphasis on inclusivity, this study examines women’s IT career decisions in Indonesia through the Individual Differences Theory of Gender and IT (IDTGIT). Using a qualitative multi-case design, 12 semi-structured interviews with female IT professionals reveal three career trajectories: stayers (women who remain in IT roles), movers (transitioning to non-IT sectors), and leavers (exiting the workforce completely). Findings show that career decisions are shaped by the interaction between internal drivers (self-actualization, personal characteristics, and career–person fit) and external contexts (organizational culture, relational support, and societal infrastructure). We found that work–family conflict and value reorientation emerge as pivotal mediators triggering transitions across career paths. This study advances IDTGIT by demonstrating its applicability in a developing, collectivist country and introducing a comparative framework across three career decisions. Practically, the findings suggest operationalizing flexible work arrangements through a Results-Only Work Environment (ROWE) and asynchronous tools, while strengthening inclusive policies via gender-responsive health support and accessible childcare to accommodate women’s dual professional and caregiving roles.